Development and validation of a clinical predictive model for 1-year prognosis in coronary heart disease patients combine with acute heart failure - Huang, Xiyi; Yang, Shaomin; Chen, Xinjie; Zhao, Qiang; Pan, Jialing; Lai, Shaofen; Ouyang, Fusheng; Deng, Lingda; Du, Yongxing; Chen, Jiacheng; Hu, Qiugen; Guo, Baoliang; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The risk factors for acute heart failure (AHF) vary, reducing the accuracy and convenience of AHF prediction. The most common causes of AHF are coronary heart disease (CHD). A short-term clinical predictive model is needed to predict the outcome of AHF, which can help guide early therapeutic intervention. This study aimed to develop a clinical predictive model for 1-year prognosis in CHD patients with AHF. Materials and Methods: A retrospective analysis was performed on data of 692 patients with AHF due to CHD admitted between January 2020 and December 2020 at a single center. After systemic treatment, patients were discharged and followed up for 1-year for major adverse cardiovascular events (MACE). The clinical characteristics of all patients were collected. Patients were randomly divided into the training (n = 484) and validation cohort (n = 208). Step-wise regression using the Akaike information criterion was performed to select predictors associated with 1-year MACE prognosis. A clinical predictive model was constructed based on the selected predictors. The predictive performance and discriminative ability of the predictive model were determined using the area under the curve, calibration curve, and clinical usefulness. Results: On step-wise regression analysis of the training cohort, predictors for MACE of AHF were diabetes, NYHA ≥ 3, HF history, Hcy, Lp-PLA2, and NT-proBNP, which were incorporated into the predictive model. The AUC of the predictive model was 0.847 (95% confidence interval (CI): 0.811–0.882) in the training cohort and 0.839 (95% CI: 0.780–0.893) in the validation cohort. The calibration curve indicated good agreement between prediction by nomogram and actual observation. Decision curve analysis showed that the nomogram was clinically useful. Conclusion: The proposed clinical predictive model accurately predicted the individualized 1-year prognosis for patients with AHF due to CHD.